"May" and "must" as inferential evidential markers in a corpus of English scientific texts - Ortega Barrera, Ivalla; Quintalla Toledo, Elena (Estudios Ingleses de la Universidad Complutense, 2013)
This paper explores the use of may and must as inferential evidential markers in the Corpus of Specialized Papers in English, currently in progress at the Institute for Technological Development and Innovation in Communications at the University of Las Palmas de Gran Canaria. In order to do so, we will follow Cornillie’s (2009) disjunctive approach to the concepts of evidentiality and epistemic modality to firstly identify evidential rather than epistemic readings of these modals. Their qualitative assessment as inferential evidential markers will be carried out through the analysis of the context in which they are immersed. We will show that appropriate contextual enrichment allows the recovery of the intended meaning, that is, mode of knowing, of both may and must.